Effect of a telerehabilitation program in sarcoidosis - Cerdan de las Heras, Jose; Balbino, Fernanda; Catalán-Matamoros, Daniel; Hilberg, Ole; Løkke, Anders; Bendstrup, Elisabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Rehabilitation is recommended in sarcoidosis to improve exercise capacity. Focus on creating flexible rehabilitation options is warranted to keep patients with sarcoidosis employed. Telerehabilitation (TR) might be an alternative. We investigated the effectiveness of TR on exercise capacity in patients with sarcoidosis. Study included stable patients with sarcoidosis who were enrolled in either a control group where they received the usual standard of care or in the 3 months TR group composed of video and chat-consultations with a physiotherapist and workout sessions with a virtual autonomous physiotherapist agent. 6-minute-walk-test (6MWT), forced-vital-capacity (FVC), diffusion-capacity-of-the-lung-for- carbon-monoxide (DLCO), isometric-voluntary-contraction (MVC), 7 days pedometry, Saint-George-Respiratory-Questionnaire for interstitial lung disease (SGRQ-I), The King’s-Brief Interstitial-Lung-Disease-Questionnaire (KBILD) and General-Anxiety-Disorder-7-Questionnaire (GAD7) were tested before and after 3 months of TR, and after 3 and 6 months follow-up. Patient-satisfaction was measured with a 5-point scale and adherence was calculated as percent of tasks and time spent training. Thirty patients aged 53.9±13.5 years, male 63.3%, FVC% 88.9±18.8, DLCO% 65.2±16.0, 6MWT 513.1±141.3 were included. Fifteen patients were randomized to TR and 15 patients to the control group. Differences in meters walked (6MWTD) between groups was at baseline (-28.9 m (p=0.58)), after 3 (+25.8 m (p=0.57)), 6 (+48.4 m (p=0.39)) and 9 months (+77.3 m (p=0.18)) follow-up in favor of TR. No differences were observed in other variables. Exercise adherence in the intervention group was 64% with an average of 28 minutes per exercise session during the first 3 months. Patient-satisfaction scored 3.8 ± 0.7. No adverse events were reported. TR did not result in any change. A statistically non-significant trend for improved 6MWTD was observed during follow-up. TR was safe, had high patient-satisfaction and acceptable adherence.